Optimized composites with the largest material usage efficiency. (April 2019) - Cui, Chaojie; Ma, Junkun; Liu, Bin
Highlights: The energy-measured material usage efficiency is proposed and provides an objective for structural optimization design. The staggered composites with rhombic platelets can make this material usage efficiency reach its upper limit, i.e. one. The widely studied staggered composites with rectangular platelets have a lower material usage efficiency since the tensile stress in the platelets and the shear stress in the matrix are generally non-uniform. Besides showing better performance based on the energy-measured material usage efficiency, the rhombic platelet case also possesses higher stiffness and strength compared with the rectangular platelet case. Abstract: This paper is aimed to seek for the optimized composite microstructure for highest material usage efficiency. An energy-measured material usage efficiency is proposed as the criterion for structural optimization design, and we believe it is the best choice among all single parameters to evaluate the performance. The staggered bio-composites consisting of rectangular platelets and soft matrix have been widely studied, and proved to possess good mechanical properties. It is found that this staggered structure can be further optimized to achieve higher material usage efficiency. Based on the shear-lag analysis, the optimization shows that the optimal platelet shape is rhombic, which leads to more uniform stresses in both the platelet and the matrix compared with the widely used platelet shape, i.e. rectangle. The rhombic platelet case also possesses higher stiffness and strength than that of the rectangular platelet case.